2014
DOI: 10.1111/nph.13213
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of asymmetrical hybridization in North American wood ferns: reconciling patterns of inheritance with gametophyte reproductive biology

Abstract: SummaryHybridization is an important evolutionary force in plants, but the mechanisms underlying it have not been well studied for many groups. In particular, the drivers of non-random patterns of interspecific gene flow (asymmetrical hybridization) remain poorly understood, especially in the seed-free vascular plants. Here, we examine patterns of asymmetrical hybridization in two widespread fern hybrids from eastern North America and study the role of gametophyte ecology in the determination of hybridization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 93 publications
(153 reference statements)
1
35
1
2
Order By: Relevance
“…This variability has been reported between species within genera (with some being highly adapted inbreeding colonists and others being highly outcrossing), as well as within particular species (e.g., Testo et al 2015). Single spores can effect long-distance migration but then subsequently incorporate new genetic diversity and become highly outcrossing (Schneller and Holderegger 1996).…”
Section: Alternation Of Generationsmentioning
confidence: 86%
“…This variability has been reported between species within genera (with some being highly adapted inbreeding colonists and others being highly outcrossing), as well as within particular species (e.g., Testo et al 2015). Single spores can effect long-distance migration but then subsequently incorporate new genetic diversity and become highly outcrossing (Schneller and Holderegger 1996).…”
Section: Alternation Of Generationsmentioning
confidence: 86%
“…If polyploids are more physiologically capable (e.g. greater hydraulic conductance, higher photosynthetic rates and increased spore production) than diploids, the former could attain an equal or greater ecological footing (DeBodt et al 2005 ;Fawcett et al 2009 ;Coate et al 2011 ;Testo et al 2014 ). Whereas some studies have shown this relationship (e.g.…”
Section: Ecological Fern Hydraulics: the Role Of Polyploidy In Fern Pmentioning
confidence: 90%
“…× shivasiae : 3.41% contraction; D . × triploidea : 0.41‐1.63% expansion; Murray, ; Redondo et al, ; Bureš et al, ; Bainard et al, ; Henry et al, ; Testo et al, ). Similar studies in the angiosperms Nicotiana and Narcissus suggest that the magnitude of genomic size change directly reflects the age of the hybrid taxon, and it may be impacted by the identity of the maternal progenitor and the degree of genetic divergence between progenitors (Leitch et al, ; Marques et al, ).…”
Section: Transcriptomic Genetic and Genomic Consequences Of Hybridimentioning
confidence: 99%